Strategi penyampaian honorifik dalam tindak perintah masyarakat tutur Makassar - Syafruddin, Syafruddin (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
Honorific informative strategies play an integral role in Indonesian speech acts within the informed families of Makassar society. These honorific informative strategies have unique characteristics. This study was conducted to describe and explain honorific informative strategies in the imperative speech acts of informed families in Makassar society. The design of this study was qualitative, applying pragmatic theory and an ethnographic communication analysis model. The results of this study show that honorific informative strategies are implemented through imperative and interrogative speech acts, using a variety of honorific alternatives based on different contexts that align with social and cultural norms.